2021
DOI: 10.1016/j.ophtha.2020.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Uveitis in Juvenile Idiopathic Arthritis

Abstract: Purpose: To assess the long-term outcome of uveitis in juvenile idiopathic arthritis (JIA). Design: Population-based, multicenter, prospective JIA cohort, with a cross-sectional assessment of JIAassociated uveitis (JIA-U) 18 years after the onset of JIA.Participants: A total of 434 patients with JIA, of whom 96 had uveitis, from defined geographic areas of Denmark, Finland, Norway, and Sweden.Methods: Patients with onset of JIA between January 1997 and June 2000 were prospectively followed for 18 years. Pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…The 18-year follow-up was composed of a study visit with clinical examination, including a full joint examination performed by experienced pediatric rheumatologists to explore whether the participants had active joints and/or restricted joints. In addition, a temporomandibular joint (TMJ) examination by a dentist, and an eye examination by an ophthalmologist were performed [22,23]. We also registered ongoing and previous medication, disease status and damage, blood tests, selfreported questionnaires on health and HRQoL, including fatigue and sleep questionnaires and participation in school/work.…”
Section: Data Collectionmentioning
confidence: 99%
“…The 18-year follow-up was composed of a study visit with clinical examination, including a full joint examination performed by experienced pediatric rheumatologists to explore whether the participants had active joints and/or restricted joints. In addition, a temporomandibular joint (TMJ) examination by a dentist, and an eye examination by an ophthalmologist were performed [22,23]. We also registered ongoing and previous medication, disease status and damage, blood tests, selfreported questionnaires on health and HRQoL, including fatigue and sleep questionnaires and participation in school/work.…”
Section: Data Collectionmentioning
confidence: 99%
“…The most recent major change in the management of childhood uveitis is the increasing use of systemic immunosuppression in children with and without JIA, and in particular the use of the antitumor necrosis factor alpha (TNF-alpha) monoclonal inhibitor, adalimumab, in refractory or severe disease. 9,10,14,15 The 2014 commencement of the multi-centre SYCAMORE (randomized controlled trial of the clinical effectiveness, safety and cost-effectiveness of adalimumab in combination with methotrexate for the treatment of juvenile idiopathic arthritis associated uveitis) trial, and the premature halt of the trial in March 2015 due to superior outcomes in the treatment group (adalimumab and methotrexate) brought increased attention to the use of systemic immunosuppressive agents in childhood uveitis. [8][9][10]16,17 A move away from infused anti-TNF agents (such as infliximab) to subcutaneous delivery of adalimumab may explain part of the early fall in hospitalizations post 2015, but not the ongoing year on year reductions in admissions.…”
Section: Discussionmentioning
confidence: 99%
“…The Nordic Study Group of Paediatric Rheumatology suggested that systematic screening for JIA-uveitis should be extended. In the Nordic JIA cohort, 12 of 434 patients had a late-onset uveitis at a mean age of 23 years, 8-18 years after the onset of JIA (Rypdal et al, 2020). Considering the additional 10 years of follow-up and that ≥5 of these 12 patients had ocular symptoms, it is not reasonable to provide systematic JIA-uveitis screening for asymptomatic adults.…”
Section: P E R S P E C T I V Ementioning
confidence: 99%
“…Uveitis occurs most commonly (82-90%) during the first 4 years after the onset of arthritis (Heiligenhaus et al, 2007;Kotaniemi et al, 2001;Nordal et al, 2017;Rypdal et al, 2020). Therefore, screening guidelines…”
mentioning
confidence: 99%